Spain and the internationalization of the economy - V. M. Tayar (Ибероамериканские тетради, 2022)
Since integration of the Spanish economy into the EU (since January 1, 1986), 35 years have already passed. During this period of time political and economic European map has undergone significant changes. Economic sectors were deeply transformed by globalization and regionalization. For Spain, the process of joining European structures mainly meant rebuilding of national economic system in accordance with the necessary criteria and norms, which set the Spanish economy on the path of diversification and modernization. In recent years, Brussels has been focusing on the growing importance of external economic and export component for the EU member–states. It means redistributing production and technological chains within the Eurozone and, furthermore, diversification of the EU trade and industrial external relations, including the demand and needs of third parties, i.e. on the markets outside the European Union. In this regard, for Spain it is of particular importance to build up its export potential, develop export clusters and extend internationalization of business, to reduce the cost of production, and intensify country’s participation in global price chains. At the same time, it is necessary to admit, that the Spanish economy and its external sector are under the pressure of both internal and external factors today. These are: protracted crisis phenomena in the European Union (Brexit, financial and economic difficulties in the Eurozone, price volatility in the energy market, etc.), the worsening conditions for interaction with the United States, trade wars, slowing global economic growth. Finally, the impact of the COVID-19 has been a major social and economic challenge for Spain.